2011
DOI: 10.1002/iroh.201011248
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Litter Decomposition of Three Riparian Tree Species and Associated Macroinvertebrates of Eswathu Oya, a Low Order Tropical Stream in Sri Lanka

Abstract: Leaf decomposition, an important component of the organic matter dynamics in streams, has been widely examined in temperate regions but much less documented in tropical regions. We report here the first study of leaf decomposition in a Sri Lankan stream. The litterbag technique was used. Coarse (8 mm) and fine (100 μm) litterbags, that included or excluded macroinvertebrates respectively, were used to enclose leaves of three dominant riparian tree species: native Ochlandra stridula (bamboo), and the introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Higher values of these variables accelerate the decomposition process, through the increase of the decomposer organisms' metabolism (Gulis and Suberkropp, 2003;Swan and Palmer, 2004). Besides this, the experimental design can influence the results, such as the use of senescent versus green leaves, the quantity of leaves used and the mesh size of the litter bags (Boulton and Boon, 1991;Walpola et al, 2011).…”
Section: Discussion Leaf Breakdownmentioning
confidence: 99%
“…Higher values of these variables accelerate the decomposition process, through the increase of the decomposer organisms' metabolism (Gulis and Suberkropp, 2003;Swan and Palmer, 2004). Besides this, the experimental design can influence the results, such as the use of senescent versus green leaves, the quantity of leaves used and the mesh size of the litter bags (Boulton and Boon, 1991;Walpola et al, 2011).…”
Section: Discussion Leaf Breakdownmentioning
confidence: 99%
“…The role of shredders is, however, variable in tropical climatic zones. Shredders have been reported as locally abundant and/or important for litter breakdown in Puerto Rico (Crowl et al, ; Cross et al, ), the Australian wet tropics (Cheshire et al, ; Camacho et al, ), Hong Kong (Li and Li, ), Malaysia (Yule et al, ), montane Ecuador (Encalada et al, ), Costa Rica (Benstead, ), Sri Lanka (Walpola et al, ) and the Colombian Andes (Chará‐Serna et al, ). However, they seem to be absent or scarce in other regions, mostly in tropical rain forests and savannas in Costa Rica (Irons et al, ; Rosemond et al, ), Colombia (Mathuriau and Chauvet, ; Rueda‐Delgado et al, ), the Brazilian Cerrado (Wantzen and Wagner, ; Gonçalves et al, ), Hong Kong (Li et al, ; Dudgeon and Gao, ), Papua New Guinea (Yule, ) and Hawaii (Larned et al, ), and in some Mediterranean streams of the Iberian Peninsula (Gonçalves et al, ; Pérez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, high microbial activities at low latitudes are counteracted by low invertebrate activities (Haapala, Muotka, & Markkola, ; Walpola, Leichtfried, Amarasinghe, & Füreder, ). Irons et al () explored litter decomposition processes in streams across a latitudinal gradient and concluded that the contribution of the invertebrates to litter decomposition increases with latitude, whereas the proportion attributable to microbes concomitantly decreases with increasing latitude (Haapala et al, ; Leite‐Rossi et al, ; Mathuriau & Chauvet, ; Tonin, Hepp, Restello, & Gonçalves, ; Walpola et al, ). Consistent with our results, for example, Boyero et al () reported unchanged decomposition rates driven by both microbes and invertebrates in an experiment across 22 sites along a latitudinal gradient (0.37–47.8°).…”
Section: Discussionmentioning
confidence: 99%